Do Characteristics And Political Background Of Regional Heads Influence Financial Performance Of Local Governments In Indonesia? - Yusnita Mahardini, Nikke; Setiawan, Doddy (International Journal of Science, Technology & Management, 2022)
The present research aims at examining the influence of characteristics and political background of regional heads on financial performance of local governments in Indonesia. The population in the present research includes local governments in Indonesia. The samples are second level of local governments in Java. The total number of final samples is 112. Data comprise the APBD realization reports, data fromofficial websites of local governments, and data from official website of the Local Government Election Commission. Panel data regression was employed for data analysis. The results of the present studyindicate that educational background and level of education exert an influence on financial performance of local governments. Meanwhile, tenure, age, and political background do not have a significant influence on financial performance of local governments. The present research was only conducted at second level of local governments in Java in 2016—2018. The present research gives contribution to the literature of local government performance, especially from the perspectives of financial performance of second level local governments in Java Island. Research on the use of political background has rarely been conducted to assess financial performance of local governments.